Morpho-physiological changes in roots of rice seedling upon submergence - Bui, Liem T.; Ella, Evangelina S.; Dionisio-Sese, Maribel L.; Ismail, Abdelbagi M. (Elsevier, 2019)
Submergence is a serious environmental condition that causes large loss in rice production in rain fed lowland and flood affected area. This study evaluated morphological and physiological responses of rice roots to submergence using two tolerant rice genotypes FR13A and Swarna-Sub 1 and two sensitive ones Swarna and IR42. The tolerant genotypes had higher survival rate and less shoot elongation but greater root elongation during submergence than the sensitive ones. After submergence, the tolerant genotypes also had higher root dry weight and more active roots than the sensitive ones. Tolerant genotypes exhibited less root injury, with less malondialdehyde production and slower electrolyte leakage after submergence. Tolerant genotypes also maintained higher concentrations of soluble sugar and starch in roots and shoots and higher chlorophyll retention after submergence than the sensitive ones. Our data showed that root traits such as root activity and root growth are associated with survival rate after submergence. This is probably accomplished through higher energy supply, and membrane integrity is necessary to preserve root function and reduce injury during submergence. These root traits are important for submergence tolerance in rice.